‘God loves you’ : in defence of theological statements - D'Cruz, Joseph Edwin (Nanyang Technological University, 2020)
Making theological statements is a contentious issue. Flew argues that since claims about God are not empirically shown and proven false using the Popperian notion of falsification, they are meaningless. I argue that falsification is an inadequate tool. The method is unable to properly falsify the very domain it is aiming to prove, namely science. I will also show how we can meaningfully make theological statements by arguing that both theology and science use analogous manners of description in their language. Keywords: theological statements, verification, falsification, analogy